2019
DOI: 10.1177/1473325019848808
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative research synthesis: An appreciative and critical introduction

Abstract: This paper introduces models and techniques for synthesizing multiple qualitative studies on a topic. Qualitative research synthesis is a diverse set of methods for combining the data or the results of multiple studies on a topic to generate new knowledge, theory and applications. Use of qualitative research synthesis is rapidly expanding across disciplines. Aggregative and interpretive models of qualitative research synthesis are defined and distinguished. Several interpretive models are detailed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
0
30
0
4
Order By: Relevance
“…This was an important step as two of the five review aims related to empirical findings. An interpretative approach was taken, in which findings of the included studies were filtered according to the conceptual assumptions and methods adopted (Drisko, 2019).…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…This was an important step as two of the five review aims related to empirical findings. An interpretative approach was taken, in which findings of the included studies were filtered according to the conceptual assumptions and methods adopted (Drisko, 2019).…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…This is a qualitative metasynthesis, a method used to create an interpretative synthesis of qualitative primary evidence in order to assist in making possible clinical decisions (12) . Therefore, the Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) recommendations were used to conduct the five stages (13) of the development of this review, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics allowed us to summarize the studies' main findings regarding their particularities and, thus, first-order concepts were identified (Figure 3). Subsequently, in an interpretative process, first-order concepts were compared and grouped, from which second-order concepts were extracted (12) . In order to construct the interpretative synthesis and understand convicts' perspectives/experiences about family relationships during the deprivation of liberty process, second-order concepts were reinterpreted in the light of a theoretical context, which allowed the elaboration of interpretative syntheses (third-order concepts) about the studied phenomenon (12) .…”
Section: Methodsmentioning
confidence: 99%
“…The self-introduction question was chosen as a theme for the analysis as Hunting (2019) and Murchison (2017) noted that self-introduction is one of the important questions to commence job interviews. Li (2002), Wodak (2013) and Drisko (2019) noted that even an excerpt that is extracted from any written textual or spoken data can represent the analysis as a whole based on the objective of the study. Therefore, in the present study, only selected excerpts were used for the analysis.…”
Section: Methodsmentioning
confidence: 99%